The Use of Aromatherapy in Reducing Stress Levels among Hemodialysis Patients: A Scoping Review - Asep Nugraha Kusdiana; Suriadi Jais; Supriadi Supriadi; Haryanto Haryanto (Journal of Innovative and Creativity, 2026)
Background: Patients with chronic kidney disease (CKD) undergoing hemodialysis are vulnerable to stress and psychological disturbances due to the long-term, repetitive, and lifelong nature of the treatment. Aromatherapy is a non-pharmacological intervention that has been applied in various clinical settings to support psychological well-being. However, the scientific evidence regarding the use of aromatherapy for stress management in hemodialysis patients remains fragmented and has not been systematically mapped. Methods: This scoping review was conducted in accordance with the Joanna Briggs Institute (JBI) methodology and reported following the PRISMA Extension for Scoping Reviews (PRISMA-ScR) guidelines. Literature searches were performed in PubMed, Scopus, and Google Scholar databases. Study selection was based on predefined inclusion and exclusion criteria. Data from included studies were extracted and analyzed descriptively to map study characteristics, intervention contexts, types of aromatherapy, and reported psychological outcomes. Results: A total of six studies met the inclusion criteria and were included in this scoping review. The included studies demonstrated variability in study design, types of essential oils used, methods of aromatherapy administration, and psychological outcome measurement instruments. Aromatherapy was predominantly administered via inhalation before or during hemodialysis sessions. Reported outcomes primarily focused on stress, anxiety, and other psychological aspects relevant to patients’ experiences during hemodialysis. Conclusion: This scoping review indicates that aromatherapy has been used as a supportive non-pharmacological intervention for stress management among hemodialysis patients; however, the available evidence remains limited and heterogeneous. Variations in intervention methods and reported outcomes highlight the need for further research using more standardized designs and a specific focus on hemodialysis populations to strengthen the evidence base in nursing practice.